PICKLE chromatin‐remodeling factor controls thermosensory hypocotyl growth of Arabidopsis. (11th September 2017) - Zha, Ping; Jing, Yanjun; Xu, Gang; Lin, Rongcheng
Abstract: Temperature is a major signal that governs plant distribution and shapes plant growth. High ambient temperature promotes plant thermomorphogenesis without significant induction of heat–stress responses. Although much progress of warm temperature‐mediated plant growth has been made during recent years, the thermomorphogenic signalling pathway is not well understood. We previously revealed that PICKLE (PKL), an ATP‐dependent chromatin remodelling factor, negatively controls photomorphogenesis in Arabidopsis thaliana . Here, we show that mutations in PKL lead to reduced sensitivity in hypocotyl elongation to warm temperature (28 °C). We demonstrate that CIRCADIAN CLOCK‐ASSOCIATED 1 (CCA1) directly binds to the specific promoter regions of PKL and its expression is reduced in the cca1 mutants. We find that the cca1 seedlings are also less sensitive to temperature‐mediated growth than the wild‐type plants. Furthermore, PKL affects the level of trimethylation of histone H3 Lys 27 associated with INDOLE‐3‐ACETIC ACID INDUCIBLE 19 ( IAA19 ) and IAA29 and regulates their expression. We also identify 6 additional transcription factors as the upstream regulators of PKL . Our study thus reveals PKL and CCA1 as 2 novel factors in controlling plant growth in response to the elevated temperature environment and provides new insight into the integration of light and temperature signals through chromatin regulation. Abstract : Temperature is a major signal that governs plant distribution and shapes plant growth. This study reveals that PKL and CCA1 are 2 novel factors in controlling plant seedling growth in response to the elevated temperature and CCA1 directly regulates PKL expression. It provides new insight into the integration of light and temperature signalling pathways through chromatin remodelling.